Once a laird - Putney, Mary Jo (Putney, Mary Jo. Rogues redeemed., 2021)
Called home to take his rightful place as laird, Kai Ramsey, returning to the remote Thorsay Islands, works together with Signy Matheson, a force to be reckoned with, for their people until unspoken desire and unexpected danger threaten to tear them apart.